2021
DOI: 10.1038/s41568-021-00363-z
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins in cancer: from biology to therapy

Abstract: Interleukins and associated cytokines serve as the means of communication for innate and adaptive immune cells as well as non-immune cells and tissues. Thus, interleukins have a critical role in cancer development, progression and control. Interleukins can nurture an environment enabling and favouring cancer growth while simultaneously being essential for a productive tumour-directed immune response. These properties of interleukins can be exploited to improve immunotherapies to promote effectiveness as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
365
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(370 citation statements)
references
References 246 publications
(266 reference statements)
3
365
0
2
Order By: Relevance
“…We therefore speculated that certain cytokines produced by inflammatory cells during PDAC initiation and progression might suppress tRF-21 production. To test this notion, we assessed the effects on tRF-21 formation of 5 inflammatory cytokines that play oncogenic roles in PDAC progression (7)(8)(9)(10)(11)(12)(13)(14), including TNF-α, IL-1α, IL-6, and IL-10, secreted by macrophages and T cells in the TME (36), and LIF, produced by tumor cells and other microenvironmental cells such as pancreatic stellate cells (12). We found that treatment of PDAC cells with LIF or IL-6 significantly inhibited tRF-21 production in a dose-dependent manner (Figure 7, A and B); however, treatment of cells with LIF or IL-6 preincubated with its neutralizing against SRSF5 verified the existence and accumulation of tRNA GlyGCC (Figure 7F).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore speculated that certain cytokines produced by inflammatory cells during PDAC initiation and progression might suppress tRF-21 production. To test this notion, we assessed the effects on tRF-21 formation of 5 inflammatory cytokines that play oncogenic roles in PDAC progression (7)(8)(9)(10)(11)(12)(13)(14), including TNF-α, IL-1α, IL-6, and IL-10, secreted by macrophages and T cells in the TME (36), and LIF, produced by tumor cells and other microenvironmental cells such as pancreatic stellate cells (12). We found that treatment of PDAC cells with LIF or IL-6 significantly inhibited tRF-21 production in a dose-dependent manner (Figure 7, A and B); however, treatment of cells with LIF or IL-6 preincubated with its neutralizing against SRSF5 verified the existence and accumulation of tRNA GlyGCC (Figure 7F).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells secrete cytokines during bacterial infections. Some cytokines affect cell proliferation and migration through autocrine mechanisms, and some act on adjacent cancer cells or noncancerous cells through paracrine mechanisms, which also play a crucial role in the development of tumors ( Briukhovetska et al, 2021 ). Casasanta et al (2020) treated HCT116 cells with F. nucleatum and detected cytokines in the culture medium.…”
Section: The Mechanisms By Which F Nucleatum Is Involved In Various Crc Stagesmentioning
confidence: 99%
“…Cancer initiation is a process primarily driven by genetic alterations of somatic cells at the site of tumor origin, but concomitant responses occur at the cellular level altering the TME [ 2 , 3 ]. For instance, increased expression of pro-inflammatory cytokines such as interleukin (IL)-1, IL-6, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α, leads to recruitment and activation of several cell types of immune and stromal cells that promote adaption of residual cells [ 4 , 5 , 6 ]. As tumors grow, genetic alterations may increase in complexity [ 7 ].…”
Section: Gastro-esophageal Adenocarcinoma (Gea)—an Introductionmentioning
confidence: 99%
“…In the process of tumor initiation, several cytokines shape a pro-tumorigenic TME with accumulation of myeloid-derived suppressor cells (MDSC) in the very initial phase, in addition to macrophages, reviewed elsewhere [ 36 , 66 , 67 , 68 , 69 , 70 , 71 ]. For instance, the pro-fibrotic and immunosuppressive transforming growth factor (TGF)-β, or the pleiotropic immune mediators IL-1 and IL-6, mediate this process [ 5 , 6 , 72 , 73 , 74 , 75 ].…”
Section: Gastro-esophageal Adenocarcinoma (Gea)—an Introductionmentioning
confidence: 99%